2009
DOI: 10.1111/j.1651-2227.2008.01119.x
|View full text |Cite
|
Sign up to set email alerts
|

Low cerebral blood flow velocity and head circumference in infants with severe hypoxic ischemic encephalopathy and poor outcome

Abstract: The high mean CBFV found in infants with severe HIE during the first days after asphyxia is temporary and low CBFV and head circumference develops by the age of 21-59 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 30 publications
(43 reference statements)
1
30
0
3
Order By: Relevance
“…In addition to the effects of vasoactive metabolites, other mechanisms, including neurogenic vasodilation, have been proposed (14). Previous studies in infants focused mainly on changes in CBF velocity (CBFV) measured using Doppler ultrasonography in infants with neonatal encephalopathy (NE) (15)(16)(17). Higher mean CBFV values have been found during the first days after asphyxia in infants with severe NE as compared with a control group of infants with mild to moderate NE and healthy infants, the maximum values of CBFV being seen at 36-72 h after birth (16,17).…”
Section: Carotid Blood Flow and Time After The Infarctionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the effects of vasoactive metabolites, other mechanisms, including neurogenic vasodilation, have been proposed (14). Previous studies in infants focused mainly on changes in CBF velocity (CBFV) measured using Doppler ultrasonography in infants with neonatal encephalopathy (NE) (15)(16)(17). Higher mean CBFV values have been found during the first days after asphyxia in infants with severe NE as compared with a control group of infants with mild to moderate NE and healthy infants, the maximum values of CBFV being seen at 36-72 h after birth (16,17).…”
Section: Carotid Blood Flow and Time After The Infarctionmentioning
confidence: 99%
“…Previous studies in infants focused mainly on changes in CBF velocity (CBFV) measured using Doppler ultrasonography in infants with neonatal encephalopathy (NE) (15)(16)(17). Higher mean CBFV values have been found during the first days after asphyxia in infants with severe NE as compared with a control group of infants with mild to moderate NE and healthy infants, the maximum values of CBFV being seen at 36-72 h after birth (16,17). More recently, using perfusionweighted imaging, Wintermark et al reported observing initial hypoperfusion followed by hyperperfusion on days 2 and 3 in infants who develop brain injury after NE (18).…”
Section: Carotid Blood Flow and Time After The Infarctionmentioning
confidence: 99%
“…12,20,21 Increased CBFV in the cerebral circulation by the age of 12 h in infants with severe HIE or poor outcome has been reported. 20,22 Increased CBFV from 24 to 72 h has been taken as a sign of permanent brain damage with poor prognosis in asphyxiated infants, [12][13][14] and the present results confirm the findings concerning increased CBFVs.…”
Section: Discussionmentioning
confidence: 99%
“…47-80% дітей, які перенесли важку асфіксію або асфіксію середнього ступня, у віці 18 місяців демонструють прояви епілепсії, дитячого церебрального параліча, зниження розумових зді-бностей, когнітивні порушення [2,4,7,9,10 ].…”
Section: вступunclassified
“…47-80% дітей, які перенесли важку асфіксію або асфіксію середнього ступня, у віці 18 місяців демонструють прояви епілепсії, дитячого церебрального параліча, зниження розумових зді-бностей, когнітивні порушення [2,4,7,9,10 ].Враховуючи наявність латентної фази при гіпоксично-ішемічних ураженнях ЦНС та ком-пенсаторні можливості дитини, важко, спира-ючись лише на клінічні дані, передбачити тяж-кість пошкодження ЦНС та спланувати час і обсяг терапевтичних втручань. Оскільки одним із найважливіших процесів, що відіграють роль у пошкодженні тканини головного мозку, є по-рушення церебральної гемодинаміки, нейросо-нографії з допплерографією, як неінвазивному, дешевому та легко здійсненому методу діагнос-тики надається велике значення.…”
unclassified